Three-dimensional True Spine Length: A Novel Technique for Assessing the Outcomes of Scoliosis Surgery. Issue 8 (December 2017) - Spurway, Alan J.; Hurry, Jennifer K.; Gauthier, Luke; Orlik, Ben; Chukwunyerenwa, Chukwudi K.; Kishta, Waleed E.; El-Hawary, Ron
Abstract : Background: Current assessment of spine growth for patients undergoing growth friendly surgical treatment for early-onset scoliosis (EOS) is the use of serial, 1-dimensional standard-of-care coronal vertical spine height (SoCVH) measurements. Any growth of the spine out of the coronal plane is missed by the SoCVH, which may underestimate the actual growth of the spine. This study set to validate the novel 3-dimensional true spine length (3DTSL) radiographic measurement technique for measuring growth of EOS patients. Methods: 3DTSL measurement accuracy, reliability, and repeatability was assessed using 10 physical model configurations. In addition, interrater and intrarater reliabilities (IRRs) were assessed using interclass coefficient (ICC) analyses of 23 retrospective EOS patient clinical radiographs. 3DTSL measurements were compared with SoCVH measurements. Results: The model assessment showed excellent accuracy with a mean error of 1.2 mm (SD=0.9; range, 0.0 to 3.0) and mean ICC of 0.999. IRR ICCs of the clinical radiographs averaged 0.952 for the 3DTSL and 0.975 for the vertical height whereas IRRs averaged 0.944 and 0.965, respectively (all P <0.001). Mean clinical 3DTSL curve lengths were 193.9 mm (SD=30.0; range, 142.8 to 276.8), whereas the SoCVH averaged 156.1 mm (SD=29.7; range, 74.7 to 207.3). The mean difference between the matched 3DTSL and SoCVH measurements was 37.8 mm (SD=21.4; range, 1.3 to 95.4) and was statistically significant ( P <0.0001). On average, the 3DTSL of the measured spines was 124.2% of the measured SoCVH, with a progressive difference as the Cobb or kyphosis angles increased. Conclusions: The novel 3DTSL measurement is accurate, repeatable, and complements the current growth assessments for EOS treatments. Level of Evidence: Level II—diagnostic study—development of a diagnostic criteria on basis of consecutive patients, with gold standard.